1992
DOI: 10.1017/s1742758400013564
|View full text |Cite
|
Sign up to set email alerts
|

Screening for plant resistance to sorghum head bug, Calocoris angustatus Leth.

Abstract: Sorghum head bug, Calocoris angustahlS Leth. (Hemiptera: Miridae) is an important insect pest of sorghum in the semi-arid tropics. A technique to screen for resistance to head bugs under fieid conditions was tested. Planting infester rows of susceptible cultivars (CSH 1 or CSH 5), 20 days before the test material or pianting early (4~5 days) fiowering lines (IS 802, IS 13429 and IS 24439) along with the test material, split planting oftest material at IS-day intervals, grouping test material according to matur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 5 publications
0
23
0
Order By: Relevance
“…Tadesse (1986) reported that loose heads of traditional cultivars had a fewer head bugs, aphids and bollworm. Sharma and lopez(1992) reported, resistant genotypes have long glumes and cover the grain over a period of 20 days after flowering, compared with 6-8 days in the susceptible controls CSH I, CSH 5, and CSH 9.…”
Section: Discussionmentioning
confidence: 99%
“…Tadesse (1986) reported that loose heads of traditional cultivars had a fewer head bugs, aphids and bollworm. Sharma and lopez(1992) reported, resistant genotypes have long glumes and cover the grain over a period of 20 days after flowering, compared with 6-8 days in the susceptible controls CSH I, CSH 5, and CSH 9.…”
Section: Discussionmentioning
confidence: 99%
“…In preliminary screening, the entries were tested under infester row technique (Sharma & Lopez, 1991b). In preliminary screening, the entries were tested under infester row technique (Sharma & Lopez, 1991b).…”
Section: Methodsmentioning
confidence: 99%
“…Selected entries were tested under no-choice conditions using the headcage technique (Sharma & Lopez, 1991b). In the advanced trials, entries were planted in 2-row plots, and replicated twice in a randomized block design.…”
Section: Methodsmentioning
confidence: 99%
“…Head bugs collected from the field were reared on CSH 1 panicles (5 pairs/panicle) at the half-anthesis stage under the headcage to raise the insect culture for these studies (Sharma et al ., 1988 ;Sharma & Lopez, 1992a) . Twenty days after infestation, bugs were collected into 200 ml plastic bottles (5 pairs in each bottle) with an aspirator from the CSH 1 panicles, and were used for infesting different genotypes .…”
Section: Insectsmentioning
confidence: 99%
“…Grain damage in the infested panicles was evaluated on a 1 to 9 scale at maturity (1 = a few grains with feeding punctures, and 9= most grains with extensive feeding, tanning and showing more than 80% shriveling) (Sharma & Lopez, 1992a ; .…”
Section: Damage Evaluationmentioning
confidence: 99%